PENYUSUNAN MODEL RUMUSAN KORELASI NILAI DCP DENGAN NILAI CBR TANAH BERBUTIR KASAR - Sujahtra, I Wayan; Redana, I Wayan; Hidayati, Anissa Maria (JURNAL SPEKTRAN, 2019)
MODEL ARRANGEMENT OF VALUE CORRELATION FORMULAS OF GRANULAR SOIL DCP – CBR   The testing of Dynamic Cone Penetrometer (DCP) in order to determine value of soil density of California Bearing Ratio (CBR) has been known widely in some countries in the world. DCP-CBR correlation formulas to determine CBR value from DCP test result has also been formulated by some researchers and the use of it has been estalished by some countries, includes Indonesia.A number of formulations of DCP-CBR correlations that have been published by a number of researchers in various countries have significant differences. It was reported that differences in geographical regions around the world caused changes in the empirical values obtained. Because of this condition therefore a research need to be done to know the correlation formulas model which is appropriate with the local soil where the writer stayed. The research result in a correlation formulas for coarse gradation soil is Log CBR = 1.514 – 1.07 Log DCP (cm/blow). This value in accordance with general formulas of some research of the world and curve graphic posisition is above and parralel with formulas correlation of PUPR.